Computational numerical analysis of drag force on a standard AeroDesign wing in accordance with winglet application - Hygor Vaz de Souza Barbosa; Júlio Cesar Costa Campos; Antonio Marcos de Oliveira Siqueira; Caio Vieira Hilário; Natália de Oliveira Faria; Bruno de Almeida Dias; Pedro Henrique Barbosa Contin Moreira (The Journal of Engineering and Exact Sciences)
This work goal is to achieve a better flight performance and to support the loading of the highest payload possible. The aerodynamics sector works to improve the aircraft aerodynamic efficiency; therefore, the aerodynamicist looks for the best solution to contribute to the aircraft efficiency by reducing drag forces. The induced drag comes from the lift force, it is related to the escape vortices which occur at the wing tips and it is the most relevant drag component. The use of structural components, as winglets, helps to reduce these vortices and the total aircraft drag. In the context of the SAE Brazil AeroDesign competition, the use of these components can support the project requirements due to the regulatory restrictions. The methodology employed was a simulation using the ANSYS CFX® software for wings modeled with different winglet configurations and the same boundary conditions to verify the best application for the studied wing. The winglet dihedral angle was set at 45°, the strings were maintained and the winglet height was used as a parameter. In the simulations, the wing attack angle was varied to obtain the variation of the drag force. With the obtained results, it was possible to verify that the wings lift forces with h=10% of the half-span winglet have lower values of drag force and present higher values of lift force, for all the analyzed angles, with a variation of up to 6 N of lift force, regarding to the wing without winglet. It is concluded the possibility to observe an improvement in the performance of the wing with the application of the winglet, in the above-mentioned context, and the compensation of a higher efficiency can help competition teams to carry more load on the aircraft due to the lift increase, and to assist the aircraft takeoff and landing handling.